The Current Israel-Palestine Conflict and its Impacts on Israel’s Economy and Diplomatic Ties - Yakubu , Muazu Adamu; Oyigebe, Peter Luke (Kashere Journal of Politics and International Relations, 2024)
The Israel-Hamas conflict begun on October 7, 2023 where there were hostilities expanding to the West Bank and the Israel-Lebanon border. Since the start of the war, it has posed serious economic and diplomatic relations for Israel. The economic implications for Israel are substantial, with an estimated weekly loss of 600 million due to work absences, representing about 6% of the country’s weekly GDP. Projections suggest that if the war extends for eight to twelve months, the overall cost to the Israeli economy could exceed 50 billion, close to 10% of the country’s GDP. Diplomatically, Israel has faced backlash, with countries like Bolivia, Belize, Türkiye, Bahrain, and Jordan taking various measures, including breaking off ties or recalling ambassadors. China and Russia have taken more assertive stances, with China playing a mediator role and Russia showing increased hostility toward Israel. The situation has raised concerns about potential mass displacement, and the conflict’s impact on the global economy is significant, potentially leading to recession. This paper examines the implication and impact of the Israel-Hamas conflict on economic and diplomatic relations of Israel, the paper leveraged on secondary sources of data cutting across scholarly submissions, News from print and New Media sources, to clearly bring to the limelight the implications of these impasse on the Middle-East and most especially a blow to Israel’s economy and diplomatic ties. Findings of the paper identify multifaceted problems to Israel, ranging from immediate human and infrastructure tolls to long-term economic and diplomatic ramifications.